KRITIK DAN RASISME DALAM ‘POÈME À MON FRÈRE BLANC’ KARYA LÉOPOLD SÉDAR SENGHOR - Sunahrowi, nfn (SUAR BETANG, 2018)
Africa literature in French-speaking especially in the field of poetry is represented by a famous and influential figure in his native country, Senegal. He was Léopold Sédar Senghor, African statesman and poet who led Senegal to independence in 1960 and became the country's first president. Senghor invites readers to experience an almost mystical and supersensory world in Africa.The research method used in Poème à Mon Frère Blanc poetry analysis by Léopold Sédar Senghor is a qualitative descriptive method. According to Moleong (2017: 6) qualitative research is used to understand the phenomenon of what is experienced by the research subject (author) in the form of behavior, perception, motivation, actions and others holistically by means of descriptions in the form of words and languages, a special natural context and utilizing various natural methods.The poem 'Poème à Mon Frère Blanc' by Léopold Sédar Senghor raises the theme about racism, namely the difference between 'black people' and 'white people' which are poured in every lyrics and words that are so enticing and critical of what has been afflicting African people who are referred to as 'colored people' in the sense of 'degrading' by white people